KECEMASAN DAN DUKUNGAN KELUARGA DENGAN KELENGKAPAN IMUNISASI DASAR BAYI PADA MASA PANDEMI COVID-19 - heni eka puji lestari; Asasih Villasari; Kartika Kartika (Dian Nuswantoro Semarang, 2022)
Basic immunization to prevent diseases in children such as measles, rubella, and diphtheria is decreasing. The Covid-19 pandemic has resulted in the training program being constrained, such as the training schedule is not good due to the closure of the technical service place. Prior coverage of diphtheria, pertussis and tetanus (DPT3) and measles and rubella (MR1) training was reduced by more than 35% in May 2020 compared to the same time period in 2016. Researchers analyzed the relationship between anxiety and family support for basic facilities for infants during the Covid-19 pandemic. Type of research is analytic observational with a cross sectional approach. The population in this study were mothers who had children aged 0-12 months who were taken by simple random sampling with a sample of 72 respondents. The variables in this study were anxiety about the impact of Covid-19, family support and complete basic equipment for infants. The measuring instrument used is a questionnaire. The test used is the Fisher's Exact Test. The results of the research on basic explanations show that most of the respondents complete the expertise of the respondents, as many as 57 (79.8%) of the total 72 respondents. There is a relationship between anxiety (p value = 0.001) and family support (p value = 0.004) with basic facilities. In conclusion, there is a relationship between the impact of covid-19 and family support for complete basic facilities for infants.